Pengaruh Dimensi Kualitas Pelayanan Terhadap Kepuasan Pelanggan : Studi Kasus pada Resto Atsiri Indonesia, Tawangmangu - Heni Valentina Samongilailai; Alexander Mario Retto Djong (Jurnal Minfo Polgan, 2026)
The purpose of this study was to investigate how customer satisfaction at Resto Atsiri Indonesia, Tawangmangu, is influenced by service quality characteristics such as tangibles, reliability, responsiveness, assurance, and empathy. Using a purposive sampling technique, 97 Partisipants were selected based on their direct experience enjoying the restaurant's dishes. A five-point Likert-scale closed-ended questionnaire that had undergone validity and reliability testing was used to collect data. Partial and simultaneous effects were tested at a 5% significance level using multiple linear regression analysis using IBM SPSS 29. The results showed that customer satisfaction was positively and significantly influenced by responsiveness. Empathy also had a positive and significant effect on customer satisfaction and was proven to be the most dominant variable based on the Standardized Beta value of 0.870. Meanwhile, tangibles, reliability, and assurance did not have a significant partial effect on customer satisfaction. Simultaneously, the five dimensions of service quality had a positive and significant effect on customer satisfaction with a contribution of 79.9% to the variation in customer satisfaction. These findings imply that the management of Resto Atsiri Indonesia needs to prioritize improving the dimensions of empathy and responsiveness through employee training oriented towards sensitivity, friendliness, and speed in serving customers to continuously increase satisfaction. Further research is recommended to add other variables such as product quality, price, and location attractiveness with a broader and more diverse scope of research objects.